CENTRAL CORNEAL THICKNESS IN METABOLIC SYNDROME POPULATION, NON-METABOLIC SYNDROME POPULATION, AND DIFFERENT BODY MASS INDEX POPULATION - KHULUQI, ROFA HUSNUL; Handayani, Nina; Anandita, Nanda Wahyu (Ophthalmologica Indonesiana, 2024)
Introduction & Objectives Central corneal Thickness (CCT) is associated with many factors including systemic disease. This study aims to evaluate and compare the CCT values in Metabolic Syndrome (MS) population, Non- Metabolic Syndrome (non-MS) population, and all different Body Mass Index (BMI) population. Methods This population-based & community service-based cross sectional study, conducted on September- November 2019 in 3 rural areas of Malang. Written informed consent was obtained from all subjects. CCT was measured with ultrasound pachymeter. The diagnosis of MS was based on International Diabetes Foundation 2006 criteria. Subjects were classified into 2 groups by MS and non-MS, also stratifed by BMI, gender, and age. Differences in CCT value between groups based on MS & non- MS, BMI, age, and gender were analyzed. Results A total of 890 subjects aged ? 40 years old were included in this study, whereas 400 subjects were diagnosed as MS (44.9%) and 490 (55.1%) others as non-MS. Mean CCT of MS were significantly greater than that of non-MS (549.743±43.22 ?m, P<0.05). Mean CCT of obese subjects were significantly greatest among other BMI groups (549.036±48.31 ?m, P<0.05). Mean CCT in women were significantly greater than that in men (546.268±39, P<0.05). Mean CCT of subjects aged 40–49 years were significantly greatest among other age groups (551.278±33,33, P<0.05). Conclusion MS population had greater CCT value as compare to non-MS population. Obese population had greatest CCT value than overweight, normal, and underweight population. These findings may have implications for understanding the relationship between CCT changes and metabolic syndrome, as well as BMI.